Gene Expression Profiling Reveals Complex Changes in the Olfactory Bulbectomy Model of Depression After Chronic Treatment With Antidepressants - Kou Takahashi; Akiyoshi Saitoh; Misa Yamada; Yoshiaki Maruyama; Noritaka Hirose; Junzo Kamei; Mitsuhiko Yamada (Elsevier, 2008)
We investigated the effects of antidepressants on the gene expression profile and behavior of olfactory-bulbectomized (OBX) rats. Removal of the main olfactory bulbs in rats alters neuronal function in brain areas involved in emotional regulation, resulting in maladaptive behavioral patterns similar to the symptoms of patients with depression. Previously, we found that OBX-induced behavioral and neuronal abnormalities were completely rescued by chronic treatment with SNC80, an opioid delta agonist, as well as with classical monoaminergic antidepressants. Thus, to determine the basis for this effect, we analyzed gene expression in OBX rat frontal cortex using a GeneChip® rat Genome oligonucleotide array after imipramine or SNC80 treatment. We found that imipramine and SNC80 induced the following systematic changes in OBX rats: zinc ion binding; hydrolase activity, acting on acid anhydrides, in phosphorus-containing anhydrides; protein serine/threonine kinase activity; N-acetyltransferase activity; protein modification process; regulation of cellular process; and regulation of neurotransmitter levels. Defining the roles of candidate neuronal systems in antidepressant-induced neural changes are likely to transform the course of research on the biological basis of mood disorders. Keywords:: antidepressant, delta opioid receptor, olfactory bulbectomy, gene expression, model animal